2014
DOI: 10.1186/preaccept-8883277521360376
|View full text |Cite
|
Sign up to set email alerts
|

New ¿- and ¿-synuclein immunopathological lesions in human brain

Abstract: Introduction: Several neurodegenerative diseases are classified as proteopathies as they are associated with the aggregation of misfolded proteins. Synucleinopathies are a group of neurodegenerative disorders associated with abnormal deposition of synucleins. α-Synucleinopathies include Parkinson's disease, dementia with Lewy bodies, and multiple system atrophy. Recently accumulation of another member of the synuclein family-γ−synuclein in neurodegenerative diseases compelled the introduction of the term γ−syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Elevated levels of NFTs, neurotoxic Aβ peptides, and loss of neurons and synapses, result in brain atrophy. These are the main factors in the progression of AD, which can be classified as a conformational disease [2] because of the roles of naturally unfolded prone to aggregation proteins in its development [3,4]. Currently, basic researchers and pharmaceutical companies have put an enormous amount of effort and funds toward finding novel targets for pharmacological interventions for AD.…”
Section: Alzheimer's Disease (Ad) Is a Devastating Neurodegenerative mentioning
confidence: 99%
“…Elevated levels of NFTs, neurotoxic Aβ peptides, and loss of neurons and synapses, result in brain atrophy. These are the main factors in the progression of AD, which can be classified as a conformational disease [2] because of the roles of naturally unfolded prone to aggregation proteins in its development [3,4]. Currently, basic researchers and pharmaceutical companies have put an enormous amount of effort and funds toward finding novel targets for pharmacological interventions for AD.…”
Section: Alzheimer's Disease (Ad) Is a Devastating Neurodegenerative mentioning
confidence: 99%
“…It also should be mentioned that based on a double‐labeling immunofluorescence study α‐syn‐positive doughnut‐shaped often ubiquitin‐positive structures were located in the GFAP‐positive, swollen processes of Bergmann glia of the cerebellum in DLB/PD and less in MSA . Furthermore, several types of oxidized‐γ‐syn positive astrocytes with different morphologies were reported in PD/DLB and also in controls . An interesting aspect of glial α‐syn immunoreactivity was highlighted by a study comparing different epitope‐retrieval methods in distinctly processed tissue: this revealed that in the normal human brain both oligodendroglia and astroglia show prominent α‐syn immunoreactivity detectable in vibratome sections using proteinase K and formic acid pretreatment .…”
Section: Pag In Non‐tauopathy Neurodegenerative Diseasesmentioning
confidence: 99%
“…The family of synuclein proteins contains α-synuclein (SNCA), β-synuclein (SNCB), and SNCG [ 6 ]. The previous 2 proteins are ubiquitously detected in both neuronal cells and presynaptic nerve terminals, where their main physiological functions are the regulation of synaptic levels of monoamine neurotransmitters through modulation of vesicular release [ 7 ]. These 2 proteins are considered to be important in certain neurodegenerative diseases, including Parkinson’s disease, Alzheimer’s disease, and dementia with Lewy bodies [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%